2018
DOI: 10.1097/meg.0000000000001183
|View full text |Cite
|
Sign up to set email alerts
|

Association of fatty liver index with the risk of incident cardiovascular disease and acute myocardial infarction

Abstract: FLI can predict incident CVD. However, the predictability of AMI using FLI is subject to interactions of metabolic factors. Individuals with FLI in the moderate to high category should be evaluated and monitored for subclinical or overt cardiovascular (including coronary) disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 31 publications
3
42
1
2
Order By: Relevance
“…More directly, NAFLD has been found to be a significant predictor of adverse CV events in middle‐aged populations, independent of age, gender, body mass index (BMI), smoking, alcohol consumption, lipid levels, or abnormal blood pressure . Thus, much evidence supports the association of NAFLD with the incidence of CVD, independent of traditional risk factors …”
Section: Studies Of the Association Between Nafld And Cardiometabolicmentioning
confidence: 99%
“…More directly, NAFLD has been found to be a significant predictor of adverse CV events in middle‐aged populations, independent of age, gender, body mass index (BMI), smoking, alcohol consumption, lipid levels, or abnormal blood pressure . Thus, much evidence supports the association of NAFLD with the incidence of CVD, independent of traditional risk factors …”
Section: Studies Of the Association Between Nafld And Cardiometabolicmentioning
confidence: 99%
“…The few cohort studies that have assessed the specific association between NAFLD and myocardial infarction recruited highly selected participants, including patients with indications for coronary angiography, with acute coronary syndrome, or with ST‐segment elevation myocardial infarction, where selection bias is a concern. In the only cohort that has specifically assessed the association between NAFLD and myocardial infarction as a single CVD event in a general population cohort, the association between NAFLD and incident myocardial infarction was weak and not statistically significant (hazard ratio [HR] 1.14, 95% CI 0.78–1.66), but this study was small and used the fatty liver index to assess fatty liver, an algorithm that is based on waist circumference, body mass index (BMI), and levels of triglyceride and gamma‐glutamyltransferase …”
Section: Introductionmentioning
confidence: 99%
“…In contrary to the above-mentioned data, NAFLD as estimated by fatty liver index was not a significant predictor of acute myocardial infarction in a long-term prospective study which also emphasized interplay of confounders [24]. Another large-scale prospective study by Chang et al has shown similar findings with insignificant association between NAFLD and CVD hospitalization after further adjusting for potential mediators [25].…”
Section: Discussionmentioning
confidence: 74%